Intuitiv eller konstrueret serendipitet? - Vick, Marion (Peripeti, 2011)
Intuitive or Constructed Serendipity? The article seeks to understand the conditions for creativity in the project Den Gemte By. How is the creative process experienced and referred to when the work deviate from the artists’ normal field? What happens to the process when well established artists’ processes are affected by factors like lack of experience, opposite expectations and ideas from new colleges? How can a theoretical analysis contribute to the development of experience from such work?